Preservative Effect of Ginger Root (Zingiber officinale R.) Extract in Refined Palm Olein Subjected to Accelerated Thermal Oxidation - Fabrice Tonfack Djikeng; Hilaire Macaire Womeni; Mallampalli Sri Lakshmi Karuna; Bernard Tiencheu; Aduni Ufuan Achidi; Michel Linder; Rachapudi Badari Narayana Prasad (Journal of Food Quality)
Oils and fats are susceptible to the oxidation of their unsaturated fatty acids during processing, storage, or handling. Oxidation reactions lead to serious damages to oil quality that makes it to be rejected by consumers for health issues and industries that might undergo financial challenges. To limit these damages, chemically synthesized antioxidants have been added to oils and fats as preservatives. However, these were reported not to be healthy and natural substitutes extracted from plant have been the main focus of many researchers and industries these recent years. This study aimed at evaluating the preservative effect of ginger root extracts in inhibiting palm olein alteration during accelerated air-dried oven storage at 180°C. The natural antioxidants were added to palm olein at the concentrations of 200, 600, 1000, 1400, and 1800 ppm and kept in the air-dried oven for six days at 180°C (daily heating was 4 h). Butylated hydroxytoluene (BHT) was used as positive control and oil with no additive functioned as the negative one. Oil samples were collected from the oven after every 2 days for analysis. The quality parameters including the peroxide value (PV), the p-anisidine value (p-AV), the total oxidation value (TOTOX), the acid value (AV), the thiobarbituric acid value (TBA), and the iodine value (IV) were determined. The changes in the fatty acid composition of palm olein were characterized by gas chromatography coupled to a flame ionization detector (GC/FID). The ginger extract was found to be effective in delaying palm olein alteration during processing. Extract efficiency was concentration-dependent and was better than that of the control and the sample supplemented with butylated hydroxytoluene (BHT). Therefore, ginger root extract can be an ideal alternative to synthetic antioxidants used in palm olein.